Hubungan Kondisi Lingkungan Fisik dengan Efisiensi Evakuasi Gempa Studi Kasus Kampung Kota Padasuka - Nirina Mutiaraafi Hasna; Moch. Ihsan Taufik Adnan; Wahyu Buana Putra (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
High-density residential areas have a high level of vulnerability to earthquake disasters, particularly when located near active faults such as the Lembang Fault in Bandung City. This study aims to analyze the effectiveness of evacuation routes and to identify potential safe assembly points within a densely populated area of Padasuka Subdistrict. The research methods include field observation, visual documentation, recording of actual evacuation routes using the Strava application (GPS tracking), and Space Syntax analysis using UCL Depthmap. The observations indicate that the area is characterized by narrow road networks, numerous dead-end streets, and a lack of open spaces, which significantly limit evacuation route options. The analysis results show that only a few main corridors have high integration and choice values, while most local paths exhibit low values, indicating network fragmentation and limited connectivity. These findings demonstrate that physical environmental conditions strongly influence evacuation effectiveness. The study concludes that evacuation routes require optimization through the creation of new access points, capacity enhancement of main corridors, and the addition of safe assembly points based on safe-radius criteria. The integration of syntactic analysis and GPS-based data is proven to be effective in formulating disaster mitigation strategies in high-density residential areas.